Optimization of Foam Properties and Evaluation of the Drying Temperature Effects on the Foam-Mat Drying of Pasta Sauce - Novita Indrianti; Devri Pramesti Putri; Lista Eka Yulianti; Nok Afifah; Lia Ratnawati; Achmat Sarifudin; Siti Khudaifanny Dasa Febrianti Asna Putri; Diah Artati; Supriyanto Supriyanto; Dede Sukarta (agriTECH, 2023)
Pasta is a convenient and ready-to-cook meal usually served with sauce. Therefore, this research aimed to explore the optimal parameters for foaming and drying through the foam-mat drying method, intending to achieve superior foam properties and convert pasta sauce into powdered form. The Central Composite Design methodology was employed to ascertain the influence of four independent variables, namely egg white concentration, CMC concentration, water-to-pasta sauce ratio, and whipping  time, on the properties of the foam. The drying conditions were orchestrated using a completely randomized design with a single factor comprising three levels, denoting drying temperatures of 50, 60, and 70 °C. The results showed that heightened egg white concentration, water-to-sauce ratio, and whipping time correlated positively with expansion volume and inversely affected foam density as well as drainage volume. Meanwhile, elevated CMC concentration exhibited a diminishing impact on expansion volume with increase in foam density and drainage volume. The optimized conditions conducive to the generation of superior foam properties were 8.99% egg white concentration, 0.1% CMC concentration, 0.54:1 ratio of water to pasta sauce, and 5 minutes of whipping time. The higher drying temperature resulted in lower moisture content, , WAI (water absorption index), and hygroscopicity of pasta sauce powder, with an increase in WSI (water solubility index) and color (lightness). The most favorable drying temperature was determined to be 60 °C, which led to a pasta sauce powder of 7.67% moisture content,  0.21, WAI 8.55 g/g, WSI 0.53%, hygroscopicity 5.65% and color (L 57.21, a 13.83, and b 16.01).